2010
DOI: 10.1176/appi.ps.61.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use Among Suicidal Adolescents: Findings From a U.S. National Community Survey

Abstract: The mental health service needs of suicidal adolescents, especially those from ethnic minority groups and lower-income families, too frequently remain unmet. Larger racial-ethnic disparities were found in use of inpatient and outpatient mental health services than in use of school-based services. Mental health services offered within school settings can reach suicidal adolescents who need services but may experience barriers to standard types of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Studies varied in time frame (i.e., current, past year, lifetime) and definitions of suicide risk (i.e., thoughts of suicide, seriously considering suicide, making plans for a suicide attempt). Based on weighted averages across the 12 studies solely assessing past-year (including current) suicide ideation, plans, and/or attempts (total N = 12,006), approximately 29.5% of individuals either sought or initiated mental health services during that same time period (n = 3546; Borges et al, 2010;Bruffaerts et al, 2011;Corna, Cairney, & Streiner, 2010;Husky et al, 2012;Kodjo & Auinger, 2004;O'Donnell, Stueve, Wardlaw, & O'Donnell, 2003;Pagura, Fotti, Katz, & Sareen, 2009;Pirkis et al, 2003;Rhodes, Bethell, & Bondy, 2006;Schweitzer, Klayich, & McLean, 1995;Wang, Hughes, Murphy, Rigby, & Langille, 2003;Wu, Katic, Liu, Fan, & Fuller, 2010). Findings from these studies-inclusive of the 12 studies assessing pastyear ideation, plans, and/or attempts, as well as those examining service use rates across varying time frames-categorized by age group, are outlined below.…”
Section: Rates Of Help-seeking and Service Utilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies varied in time frame (i.e., current, past year, lifetime) and definitions of suicide risk (i.e., thoughts of suicide, seriously considering suicide, making plans for a suicide attempt). Based on weighted averages across the 12 studies solely assessing past-year (including current) suicide ideation, plans, and/or attempts (total N = 12,006), approximately 29.5% of individuals either sought or initiated mental health services during that same time period (n = 3546; Borges et al, 2010;Bruffaerts et al, 2011;Corna, Cairney, & Streiner, 2010;Husky et al, 2012;Kodjo & Auinger, 2004;O'Donnell, Stueve, Wardlaw, & O'Donnell, 2003;Pagura, Fotti, Katz, & Sareen, 2009;Pirkis et al, 2003;Rhodes, Bethell, & Bondy, 2006;Schweitzer, Klayich, & McLean, 1995;Wang, Hughes, Murphy, Rigby, & Langille, 2003;Wu, Katic, Liu, Fan, & Fuller, 2010). Findings from these studies-inclusive of the 12 studies assessing pastyear ideation, plans, and/or attempts, as well as those examining service use rates across varying time frames-categorized by age group, are outlined below.…”
Section: Rates Of Help-seeking and Service Utilizationmentioning
confidence: 99%
“…The National Comorbidity Survey-Adolescent Supplement (NCS-A), which surveyed 10,123 United States adolescents aged 13-18 years, found that in the past year, only 32.7% of adolescents with suicidal ideation, 45.6% with a plan, and 43.1% who had made an attempt in the past year reported having had contact with a mental health care provider (Husky et al, 2012). Similarly, the National Household Survey on Drug Abuse (NHSDA) found that only 45% of United States adolescents (N = 877) aged 12-17 years who had attempted suicide in the previous year had used mental health services during that same time frame (Wu et al, 2010). Studies conducted in Canada, the United Kingdom, and Mexico have also found rates of mental health service use among adolescents and young adults with suicidal ideation and behaviors to be at or below 50% (Biddle, Gunnell, Sharp, & Donovan, 2004;Borges et al, 2010;Cheung & Dewa, 2007).…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not accepting or accessing available helping resources might have been due to the affected person's doubt about the efficacy of treatment (Rudd et al 1995), maladaptive coping strategies of suicidal people (Gould et al 2004;Rudd et al 1995), negative attitudes towards or beliefs about seeking professional help (Carlton and Deane 2000;Wilson) or stigma associated with suicidality (Sudak et al 2008). Low utilization of professional health services among suicidal people has also been described in earlier studies (Borges et al 2010;Husky et al 2012;Johnston et al 2009;Pirkis et al 2003;Wu et al 2010). …”
Section: Discussionmentioning
confidence: 79%
“…Low rates of formal help-seeking among suicidal people (Borges et al 2010;Husky et al 2012;Johnston et al 2009;Pirkis et al 2003;Wu et al 2010) or among people with significant mental health problems Essau 2005;Wang et al 2007;Zachrisson et al 2006) indicate that those who might need help are not accepting or accessing available resources. By contrast, other studies about actual helpseeking behaviour have not found an inverse association between levels of suicidality or mental health problems and help-seeking (Borges et al 2010;Burgess et al 2009;Husky et al 2012;Johnston et al 2009;Pirkis et al 2003;Wang et al 2007;Zachrisson et al 2006).…”
Section: Introductionmentioning
confidence: 99%